High Energy Density Dielectrics Based on PVDF‐Based Polymers. Issue 5 (26th April 2018) - Hu, Xinping; Yi, Kewang; Liu, Jie; Chu, Baojin
Abstract: Many applications, such as hybrid vehicles, pulsed power generators, and power factor correction, require capacitors with high energy density to reduce the size or weight of the related systems. For these applications, dielectric film capacitors are often used because of their fast discharge speed and high power density. The energy density of commercial available film capacitors is relatively low and cannot meet the demands for those applications. In the past decade, different polymer‐based dielectric materials have been intensively investigated to improve the energy density of the materials. Here, the progress in developing high energy density polymer‐based dielectric materials is reviewed, and strategies to improve the energy density of dielectric polymers are summarized and discussed. Because polyvinylidene fluoride (PVDF)‐based polymers have relatively high dielectric properties and have been intensively studied for the energy storage applications, the discussion focuses mainly on PVDF‐based polymers and composites. An outlook for the future directions and problems that will be tackled to further improve the energy density of dielectrics is also provided. Abstract : Polyvinylidene fluoride (PVDF)‐based polymers and their composites have been intensively investigated for energy storage applications. The recent progress in the development of high‐energy‐density dielectric materials for energy storage and pulse power applications based on PVDF‐based polymers and composites is reviewed and different strategies to improve the energy density are discussed.